Relationship between baseline severity of depression and antidepressant treatment outcome - Henkel, Verena; Seemüller, F.; Obermeier, M.; Adli, M.; Bauer, M.; Kronmüller, Klaus-Thomas; Holsboer, F.; Brieger, P.; Laux, G.; Bender, W.; Heuser, I.; Zeiler, J.; et al. (Pharmacopsychiatry, 2011)
Thieme E-Books & E-Journals